ä»¥é©¬å†…åˆ©ä¸ä¸“äºŒæ ¡æ±‰è¯æ•™æç ”ç©¶åˆ†æž - Derianto, Derianto; Ina, Ina; Suhardi, Suhardi (Universitas Tanjungpura, 2024)
The teachers, modules, and the students are three important learning characteristica. Modules are the materials for learning and guidance to the students and can add to the students' knowledge which can be in the form of writing, sound, things based on definite scientific aspects and put together into a book. Choosing the suitable module that suits the students is one of the significant responsibilities of the teachers. It is because the selected module can affect the entire learning process.